Pathogenesis, diagnosis, dietary management, and prevention of gastrointestinal disorders in the paediatric population - Giulio Pulvirenti; Vincenzo Sortino; Sara Manti; Giuseppe Fabio Parisi; Maria Papale; Alessandro Giallongo; Salvatore Leonardi (BMC, 2022)
Abstract Nutrition has a central role in child growth with long-term effects, and nutrition management in gastrointestinal disorders has great importance for child health and disease outcomes. Breast milk is the first choice for infant nutrition. When it is not available, special milk formulas are adopted in specific conditions, as a medical treatment. Moving from the strong guidelines, recommendations and the new possibilities of special diet treatment, this review will analyse the current diet treatment in different gastrointestinal disorders, including food allergy, cystic fibrosis, inflammatory bowel diseases, short-bowel syndrome, gastroesophageal reflux, and eosinophilic esophagitis. The review also aimed at understanding the role of diet and its effects on these diseases. The growth monitoring can prevent malnutrition and improve disease outcomes, particularly in children, and an appropriate dietary management targeted to specific disorders is the best therapeutic choice alone or in combination with pharmacological therapy.